HETEROTOPIC PREGNANCY- A REPORT OF 2 CASES IN WOMEN WITHOUT RISK FACTORS - Bukhari, Afzal Safdar; Bukhari, Shazia (Journal of Ayub Medical College Abbottabad, 2001)
Two cases of heterotopic pregnancy are reported. The cases emphasize that co incident pregnancies may occur in women who are without risk of ectopic pregnancy or multiple gestation. The cases describe the complexities of diagnosis and management.